IMPLEMENTASI PEMBELAJARAN BERNYANYI MATA PELAJARAN SENI BUDAYA DAN PRAKARYA BERBASIS KEARIFAN LOKAL SENI KOMPANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR: ANALISIS STRATEGI PEDAGOGIS DAN EFEKTIVITAS KURIKULER - Mitra Karlisa; Desty Dwi Rochmania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Music learning within the Seni Budaya dan Prakarya curriculum at the elementary school level encounters significant challenges related to the effectiveness of instructional methods and the relevance of teaching materials to local cultural contexts. This study aims to analyze the implementation of singing instruction integrated with local wisdom through Kompang art in order to enhance the learning outcomes and motivation of fifth-grade students. Employing a cooperative learning classroom action research design conducted in two cycles, the study involved 30 students as the primary subjects. Data were collected through participatory observation, learning achievement tests, and in-depth interviews. The findings indicate an improvement in the class average score from 70 in the first cycle to 85 in the second cycle, with notable increases in intonation (25.00%) and vocal technique (23.08%). The contextual teaching and learning approach and the integration of Kompang cultural representation were found to be effective in facilitating students’ transition from basic cognitive understanding to more complex vocal psychomotor mastery. These results affirm that the synchronization between constructivist theory proposed by Lev Vygotsky and the reinforcement of local cultural identity through traditional arts can create a more inclusive and meaningful learning environment while addressing the issue of students’ low interest in traditional arts in the era of globalization.